Inspection At Summerhill - Keeble-Ramsay, Diane; Zilocchi, Fabiana (Revista Hipótese, 2018)
This paper considers issues surrounding the 1999 OFSTED inspection ofSummerhill school (in Suffolk) which led to a Notice of Closure, and subsequent successfulappeal on the grounds of inappropriate judgements made by OFSTED inspectors. It isuseful to note that Summerhill School has existed in the independent sector offering‘progressive education’ since the 1920s. However, following a 1990s inspection fromOFSTED, its existence was threatened in terms of its freedom in future continuing to offeran independent UK-based fully ‘democratic’ schooling (despite the fact that parents pay fortheir children to attend Summerhill outside any UK state offering). This paper identifiesproblems for organisationssubject to inspection which do not conform to the formalorganisation model.
Keywords: Summerhill; School Effectiveness; Independent School Inspection